International journal of human resource management (Routledge, 1990)
Concerned with the expanding role of strategic human resource management in a fast-changing global environment, the journal focuses on future trends in human resource management, drawing on empirical research in the areas of strategic management, international business, organizational behaviour, personnel management and industrial relations that arise from internationalization, technological change, market integration, new concepts of line management, increased competition, and changing corporate climates.